2004
DOI: 10.1177/0898264303260448
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent and Long-Term Predictors of Older Adults’ Use of Community-Based Long-Term Care Services

Abstract: Caregiver-related need variables play a significant role in defining utilization patterns of community-based long-term care services among older adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
71
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(83 citation statements)
references
References 40 publications
9
71
0
3
Order By: Relevance
“…The widely adopted Andersen behavioral model (1995) suggests gender is a predisposing factor that influences health service use. However, empirical studies to date have not found a relationship between gender and overall formal service use (Bookwala et al, 2004;Tennstedt, Crawford, & Delgado, 1998). Thus, if gender differences exist, they may be contingent on the specific type of formal service under examination.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
“…The widely adopted Andersen behavioral model (1995) suggests gender is a predisposing factor that influences health service use. However, empirical studies to date have not found a relationship between gender and overall formal service use (Bookwala et al, 2004;Tennstedt, Crawford, & Delgado, 1998). Thus, if gender differences exist, they may be contingent on the specific type of formal service under examination.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
“…We assessed the impact of predisposing, enabling factors as well as need (Andersen, 1995;Andersen & Newman, 2005;Bass & Noelker, 1987;Bookwala et al, 2004;Geerlings et al, 2005;Geerts & Van der Boch, 2012;Suanet et al, 2012;Hlebec, 2012;Hlebec, 2014) on preferences for care arrangements, focusing on community and organisational enabling factors. To evaluate care arrangements, empirical distributions of care arrangements across all 22 tasks were computed and coded into eight empirically possible care arrangements (Jacobs et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…We also evaluated care arrangements across separate task areas (AADL, IADL and PADL). Care arrangements were defined as follows (Table 1 Like other studies, we constructed the independent variables in the model (Andersen, 1995;Andersen & Newman, 2005;Bass & Noelker, 1987;Bookwala et al 2004;Geerlings et al, 2005;Geerts & Van der Boch, 2012;Suanet et al, 2012;Hlebec, 2012;Hlebec, 2014). We included the following predisposing factors: age, gender, and level of education.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A taxonomia referida em estudos anteriores para identificação de fatores associados ao consumo de recursos segue a abordagem definida nos trabalhos realizados por Andersen e Newman [23] e Andersen [24], que consideram três componentes principais: fatores predisponentes, condições propícias e fatores associados a necessidades específicas [20,[25][26][27]. Na categoria dos fatores predisponentes estão incluídas as características individuais tal como a etnia, a idade e o estado civil [25].…”
Section: Introductionunclassified